Quality Controls in Digital Mammography protocol of the EFOMP Mammo Working group. (April 2018) - Gennaro, Gisella; Avramova-Cholakova, Simona; Azzalini, Andrea; Luisa Chapel, Maria; Chevalier, Margarita; Ciraj, Olivera; de las Heras, Hugo; Gershan, Vesna; Hemdal, Bengt; Keavey, Elizabeth; Lanconelli, Nico; Menhart, Susanne; et al.
Highlights: The EFOMP protocol on Quality Control in digital mammography is presented. The protocol is simple and applicable to any type of digital mammography system. The protocol provides clear instructions about each test procedure, in order to minimize the potential for misinterpretation. Abstract: This article aims to present the protocol on Quality Controls in Digital Mammography published online in 2015 by the European Federation of Organisations for Medical Physics (EFOMP) which was developed by a Task Force under the Mammo Working Group. The main objective of this protocol was to define a minimum set of easily implemented quality control tests on digital mammography systems that can be used to assure the performance of a system within a set and acceptable range. Detailed step-by-step instructions have been provided, limiting as much as possible any misinterpretations or variations by the person performing. It is intended that these tests be implemented as part of the daily routine of medical physicists and system users throughout Europe in a harmonised way so allowing results to be compared. In this paper the main characteristics of the protocol are illustrated, including examples, together with a brief summary of the contents of each chapter. Finally, instructions for the download of the full protocol and of the related software tools are provided.